Effects of Prostaglandins, Derivatives of Cyclic 3':5'-AMP, Theophylline, Cholinergic Agents and Colchicine on Clot Retraction in Dilute Platelet-Rich Plasma and Gel-Separated Platelet Test Systems - Moake, J. L; Cimo, P. L; Widmer, K; Peterson, D. M; Gum, J. R (Thrombosis and Haemostasis, 1977)
In dilute suspensions of platelet-rich plasma (PRP) or gel-separated platelets (GSP), dibutyryl-cAMP (DBcAMP) and monobutyryl-cAMP inhibited platelet-mediated fibrin clot retraction in concentrations of 2–3 × 10–6M, with complete inhibition at 1–3 × 10–4M. Prostaglandin E1 (PGE1), which inhibited fibrin clot retraction in concentrations greater than 1.5–3 × 10–8M, was a more effective inhibitor than either PGE2 or PGF2α. In the presence of theophylline (10–4M), concentrations of DBcAMP, PGE1 PGE2 and PGF2α necessary to inhibit fibrin clot retraction were reduced 50-fold for DBcAMP and 2.5 to 20-fold for the prostaglandins. In dilute PRP or GSP, inhibition of fibrin clot retraction does not result from inhibition of thrombin-induced platelet aggregation. Thus, compounds which increase platelet cAMP levels result in the inhibition of platelet-mediated fibrin clot retraction, and this inhibitory effect may be mediated, at least in part, through suppression of platelet contractility. Cyclic GMP, dibutyryl-cGMP and carbamylcholine-Cl (which stimulates guanylate cyclase) did not influence fibrin clot retraction, and did not prevent inhibition of fibrin clot retraction by DBcAMP and PGE?. Colchicine, in concentrations known to disrupt platelet microtubules (2.5 × 10–6M to 2.5 x 10–3M), had little inhibitory effect on either fibrin clot retraction or platelet (3H)-serotonin release.